Повышение экономичности топливоиспользования в промышленных печах - Димитров, А. Д.; Шраменко, А. Н.; Пядухов, В. А. (НТУ "ХПИ", 2015)
Рассмотрено влияние предварительного подогрева материала и подогрева компонентов горения за счёт теплоты уходящих газов на экономию топлива в промышленных печах при известных значениях коэффициента регенерации и коэффициента полезно использованной теплоты рабочей камеры. В выводах сделаны рекомендации по выбору целесообразного способа внутреннего использования теплоты уходящих из рабочей камеры продуктов сгорания с позиций повышения производительности печи и экономии топлива.

The comparison data of different options of the internal use of the heat of effluent combustion products during the operation of high temperature thermal process plants (HTTP) have been given. The main factors that affect the efficiency of the heat use during the operation of HTTP have been defined. On the bases of balance equations the methods of the computation of the fuel saving at the preliminary material heating and the heating of burning components due to the regeneration of heat of effluent combustion products have been given. The influence of a coefficient of heat regeneration and a coefficient of the efficiently used heat of the working chamber on the value of the relative heat of effluent combustion products (appropriate diagrams and design ratio are given) was shown. The conclusion section gives the recommendations for the selection of the efficient method for the internal use of the heat of combustion products effluent from the working chamber from the standpoint of an increase in the HTTP productivity and fuel saving.
Increasing the efficiency of the fuel use for industrial furnaces
Keywords: печные установки; экономия топлива; уходящие газы; рекуперация тепла; fuel saving; furnace; combustion products; recuperation